2013
DOI: 10.1002/jts.21871
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of a Postdisaster Intervention on Risk and Resilience Factors Associated With Posttraumatic Stress Disorder in Chinese Children

Abstract: This study is an evaluation of a psychosocial intervention involving child and adolescent survivors of the 2008 Sichuan China earthquake. Sociodemographics, earthquake-related risk exposure, resilience using the Connor-Davidson Resilience Scale, and posttraumatic stress disorder (PTSD) using the UCLA-PTSD Index were collected from 1,988 intervention participants and 2,132 controls. Mean resilience scores and the odds of PTSD did not vary between groups. The independent factors for risk and resilience and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
17
0
1
Order By: Relevance
“…Considering the previous findings, the effect of intervention in this study may be relevant to the observed increase in resilience. Fu et al . suggested that awareness of one's own mental health and communicating with others about one's psychological state may enhance resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the previous findings, the effect of intervention in this study may be relevant to the observed increase in resilience. Fu et al . suggested that awareness of one's own mental health and communicating with others about one's psychological state may enhance resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the previous findings, the effect of intervention in this study 19,20 may be relevant to the observed increase in resilience. Fu et al 38 suggested that awareness of one's own mental health and communicating with others about one's psychological state may enhance resilience. The mental health of the students was assessed annually for 3 years after the disaster using the CD-RISC-10, QIDS-J, SAS, and IES-R, which may have provided opportunities for self-awareness and facilitated help seeking among the students.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite there being a great number of studies on the psychometric properties of the CD-RISC, there is still a great lack of consensus on the internal structure of the scale, since most studies in the literature reveal different factorial structures. Empirical evidence has supported the onedimensional model (Arias-Gonzalez, Crespo-Sierra, Arias-Martinez, Martinez-Molina & Ponce, 2015;Burns and Anstey, 2010;Campbell-Sills & Stein, 2007;Gucciardi, Jackson, Coulter & Mallett, 2011;Notario-Pacheco et al, 2011;Ponce-Cisternas, 2015;Sarubin et al, 2015), the twodimensional model (Fu, Leoutsakos & Underwood, 2013;Green et al, 2014;Jorgensen & Seedat, 2008;Perera & Ganguly, 2016), the three-dimensional model (Karairmak, 2010;Mealer, Schmiege & Meek 2016;Menezes de Lucena et al, 2006;Serrano-Parra et al, 2012;Xie, Peng, Zuo & Li, 2016;Yu & Zhang, 2007), the four-dimensional model (Crespo et al, 2014;Khoshouei, 2009;Lamond et al, 2008;Singh & Yu, 2010;Solano et al, 2016), the five-dimensional model (Fujikawa et al, 2013;Gillespie, Chaboyer, Wallis & Grimbeek, 2007;Jung et al, 2012;Manzano-García & Ayala-Calvo, 2013) and the second-order model (Yu et al, 2011). According to the above list, one could believe that the CD-RISC presents a different factorial configuration between studies, countries or sample types and therefore it would lead one to further believe that, in each case, one is measuring different constructs.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have shown that resilience is consistently associated with positive trauma-related outcomes (Masten and Coatsworth, 1998;Masten, 2001;Herrenkohl, 2011). In particular, it is associated with adaptive outcomes among children who are victims of violence (Ellenbogen et al, 2014; and other trauma (Wolmer et al, 2011;Baum et al, 2013;Fu et al, 2013;Sanderson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%